Prospective Evaluation of a Novel Unidirectional Permanent Device for Intraoperative Brachytherapy - Abraham J. Wu, MD; Irini Youssef, MD; Gil’ad N. Cohen, MS; Paul B. Romesser, MD; Neil K. Taunk, MD; Karen Episcopia, MS; Christopher H. Crane, MD; Philip Paty, MD; Julio Garcia-Aguilar, MD, PhD; Martin Weiser, MD; J. Joshua Smith, MD, PhD; Garrett M. Nash, MD; et al. (Advances in Radiation Oncology)
Purpose: The CivaSheet is a novel radiation delivery device consisting of unidirectionally shielded Pd-103 sources embedded in a bioabsorbable polymer sheet. This facilitates intraoperative placement of permanent brachytherapy seeds in a surgical tumor bed, while minimizing dose to overlying structures. No clinical trial data have yet been published for this device. We prospectively investigated its feasibility as an alternative to standard intraoperative radiation therapy (IORT). Methods and Materials: This was a prospective study in patients with abdomopelvic malignancies undergoing surgery with an indication for IORT. Prior external beam radiation was allowed. The primary endpoint was feasibility, defined as technically satisfactory placement of CivaSheet in ≥7 of 10 patients. Secondary endpoints were adverse events, local control, and implant stability. Results: Ten patients were enrolled and underwent surgery. Eight patients successfully underwent CivaSheet implantation. The 2 feasibility exclusions were technically unfavorable based on intraoperative assessment of tumor bed configuration. All implanted patients were treated to the pelvic sidewall or presacral space with a median prescription dose of 100 Gy. Median follow-up from the date of implant was 25 months. One patient had a marginal recurrence 3 months after implant, and 1 patient recurred at implant site after 13 months. One and 2-year estimates of local control were 86% and 69%, respectively. No device-related grade 4-5 adverse events were observed. Postimplant stability was deemed satisfactory in all patients. Conclusions: This is the first published clinical trial of a novel unidirectional brachytherapy device. CivaSheet proved to be a feasible technique to deliver intraoperative radiation to patients with high-risk pelvic malignancies after surgical resection, and warrants further study and clinical consideration, particularly in settings where other IORT options are not available.